Monetary policy, composite leading economic indicators and predicting the 2001 recession - Mostaghimi, M (Journal of Forecasting, 2004)
On 26 November 2001, the National Bureau of Economic Research announced that the US economy had officially entered into a recession in March 2001. This decision was a surprise and did not end all the conflicting opinions expressed by economists. This matter was finally settled in July 2002 after a revision to the 2001 real gross domestic product showed negative growth rates for its first three quarters. A series of political and economic events in the years 2000-01 have increased the amount of uncertainty in the state of the economy, which in turn has resulted in the production of less reliable economic indicators and forecasts. This paper evaluates the performance of two very reliable methodologies for predicting a downturn in the US economy using composite leading economic indicators (CLI) for the years 2000-01. It explores the impact of the monetary policy on CLI and on the overall economy and shows how the gradualness and uncertainty of this impact on the overall economy have affected the forecasts of these methodologies. It suggests that the overexposure of the CLI to the monetary policy tools and a strong, but less effective, expansionary money policy have been the major factors in deteriorating the predictions of these methodologies. To improve these forecasts, it has explored the inclusion of the CLI diffusion index as a prior in the Bayesian methodology. Copyright (C) 2004 John Wiley Sons, Ltd.
10 citations (Crossref) [2023-10-31] tex.unique-id: ISI:000225169500001
Keywords: Bayesian probability forecasting; Classical statistical decision theory; Composite leading indicators; Composite leading indicators (CLI); Composite leading indicators diffusion index; Diffusion index; Geochronology; Industrial economics; Information theory; Monetary policy; Predicting recessions; Probability; Public policy; Quality control; Set theory; Statistical methods; US economy; Us economy; dept.eco; dept.fin

Orange county bankruptcy: financial contagion in the municipal bond and bank equity markets - Halstead, John M; Hegde, Shantaram P; Klein, Linda S (The Financial Review, 2004)
We examine the spillover wealth effects of the Orange County, California bankruptcy announcement in December 1994 on municipal bonds, municipal bond funds, and bank stocks. This bankruptcy is prominent because of unprecedented losses and because it was caused by a highly leveraged derivatives strategy rather than a shortage of tax revenues and excess spending. We find contagion in the bond market with significantly negative abnormal returns for municipal bond funds without direct exposure to Orange County and for non-Orange County municipal bonds. In addition, our findings suggest the contagion spills over to the common stocks of investment and commercial banks that deal in or use derivatives; however, the equities of banks unexposed to derivatives are not affected. © 2004 Blackwell Publishing Ltd.
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-297-207-159-99X tex.type: [object Object]
Keywords: Bank equity; Contagion; Derivatives; Fixed income; G2/H3/K2; Municipal financing; dept.eco; dept.fin